Partners in teaching and learning coordinating a successful academic library - Mallon, Melissa N. (Beta Phi Mu scholars series, 2020)
"Instruction coordinators & directors in academic libraries may have a variety of titles and wear an entire wardrobe's worth of hats, but we face many of the same challenges in developing, promoting, and evaluating our instruction programs"--